Analisa Pola Konsumsi Generasi Y Terhadap Produk pada Industri Halal di Indonesia (Studi Kasus di Sekolah Tinggi Ekonomi Islam (Stei) Tazkia - Annisa Ristiana; Abdurrahman Misno; Endri Endri (Jurnal Indonesia Sosial Sains, 2022)
Generation Y was born in 1977-1994 (Pramesty & Simanjuntak, 2020). The main characteristic of Generation Y is that they actively use the internet and technology to help fulfill their needs, include daily consumption goods. Generation Y is prefers online shopping than conventional. Indonesia, a Muslim-majority country, has much Muslims Generation Y and has high demand for halal products that can be purchased online. The purpose of this research is to analyze the factors that influence the consumption of halal industrial products in Indonesia. The data were analyzed by using multiple linear regressions. The results of the regression test showed that had a positive/significant effect in income, yet no effect in academic qualifications. The dummy variables of gender, occupation, marital status and purchased products showed that there was no difference. Income has a positive/significant influence on the consumption pattern of Generation Y towards products in the halal industry in Indonesia. While the academic achievement variable and the four dummy variables namely gender, occupation, marital status and purchased products, who buy products through online shops, marketplaces and e-commerce do not have a positive/significant influence on the pattern of consumption in generation Y.